Using coordination measures for movement analysis - Hamill, J.; Haddad, J. M.; van Emmerik, R. A. A. (ISBS - Conference Proceedings Archive (Konstanz), 2005)
Traditionally, in biomechanics we have investigated the actions of single joints or segments without taking into account the interactions of these structures. A dynamical systems approach has been increasingly used in biomechanics to give a different perspective on the interaction of specific structures in human movement. That is, the study of coordination has become more prominent in the biomechanics literature based on the work of Bernstein (1967). Coordination is defined as overcoming excessive degrees of freedom thereby turning individual movement elements into a controllable system. In this paper, we will describe a theoretical framework for analyzing coordination, present examples in the literature and discuss future developments for this type of analysis.